2019
DOI: 10.5194/acp-19-5187-2019
|View full text |Cite
|
Sign up to set email alerts
|

Identification and quantification of particulate tracers of exhaust and non-exhaust vehicle emissions

Abstract: Abstract. In order to identify and quantify key species associated with non-exhaust emissions and exhaust vehicular emissions, a large comprehensive dataset of particulate species has been obtained thanks to simultaneous near-road and urban background measurements coupled with detailed traffic counts and chassis dynamometer measurements of exhaust emissions of a few in-use vehicles well-represented in the French fleet. Elemental carbon, brake-wear metals (Cu, Fe, Sb, Sn, Mn), n-alkanes (C19-C26), light-molecul… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
67
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 123 publications
(80 citation statements)
references
References 88 publications
11
67
0
2
Order By: Relevance
“…In order to conduct a comparison, the emission factors for n-alkanes have been converted from µg/kg fuel to µg/km travelled using a vehicle fuel consumption of 0.06 kg.fuel/km and assuming that the engine runs for 33% of time at low load and the remainder at high load. The estimated emission factors appear in Table S3, and can be compared with particle phase data for n-alkanes of C19-C26 reported by Charron et al 48 for Euro 3 (E3) and Euro 4 (E4) diesel passenger cars with a DOC and Euro 4 with a DOC and DPF. The two vehicles with DOC only tested by Charron et al 48 showed markedly different concentrations both peaking a C21 with emission factors (EF) of 31.5 (E3) and 5.84 (E4) µg/km for the C21 n-alkane.…”
Section: Comparison Of Emission Factors With Other Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…In order to conduct a comparison, the emission factors for n-alkanes have been converted from µg/kg fuel to µg/km travelled using a vehicle fuel consumption of 0.06 kg.fuel/km and assuming that the engine runs for 33% of time at low load and the remainder at high load. The estimated emission factors appear in Table S3, and can be compared with particle phase data for n-alkanes of C19-C26 reported by Charron et al 48 for Euro 3 (E3) and Euro 4 (E4) diesel passenger cars with a DOC and Euro 4 with a DOC and DPF. The two vehicles with DOC only tested by Charron et al 48 showed markedly different concentrations both peaking a C21 with emission factors (EF) of 31.5 (E3) and 5.84 (E4) µg/km for the C21 n-alkane.…”
Section: Comparison Of Emission Factors With Other Studiesmentioning
confidence: 99%
“…The estimated emission factors appear in Table S3, and can be compared with particle phase data for n-alkanes of C19-C26 reported by Charron et al 48 for Euro 3 (E3) and Euro 4 (E4) diesel passenger cars with a DOC and Euro 4 with a DOC and DPF. The two vehicles with DOC only tested by Charron et al 48 showed markedly different concentrations both peaking a C21 with emission factors (EF) of 31.5 (E3) and 5.84 (E4) µg/km for the C21 n-alkane. This compares with EFs of 29.2 (before DOC) and 4.0 µg/km (after DOC and DPF) in our data (Table S3), suggesting high comparability.…”
Section: Comparison Of Emission Factors With Other Studiesmentioning
confidence: 99%
“…One possible explanation is that low temperature condition promotes gas-particle partitioning and changes the particle phase reaction. The gas-phase OH oxidation can reduce H/C and increase O/C ratios (Heald et al, 2010;Lambe et al, 2015;Li et al, 2018), while particle-phase oligomerization almost won't change O/C and H/C ratios (Charron et al, 2019). Under high temperature condition, more gas-phase oxidation steps are needed to produce the less volatile products to condense into particle-phase (because of the high temperature, i.e., high saturation vapor pressure).…”
Section: Temperature Effect On Chemical Composition and Reaction Mechmentioning
confidence: 99%
“…The observations above showed that the scattering property of formed SOA increased under lowtemperature conditions, which might provide one possible reason for the rapid occurrence of haze in suburban areas in winter. According to field observations, haze frequently occurs in winter, especially in China (Cheng et al, 2016;Huang et al, 2014;Guo et al, 2014;Parrish et al, 2007). When haze occurs, it is often accompanied by high-NO x conditions, especially in urban areas.…”
Section: Atmospheric and Climate Implicationsmentioning
confidence: 99%
“…Aerosol physicochemical properties are strongly dependent on the atmospheric conditions, such as the relative humidity (Ervens et al, 2011;Sun et al, 2014), temperature (Wang et al, 2017) and oxidizing conditions, the latter of which includes the oxidant type, e.g., NO 3 , OH and O 3 , and the oxidation concentrations, e.g., photochemical age (Cheng et al, 2016;Shrivastava et al, 2017;George et al, 2015;Kanakidou et al, 2005). Therefore, it is important to study SOA formation and optical properties under varying atmospheric conditions to simulate the processes in the real atmosphere.…”
Section: Introductionmentioning
confidence: 99%